The effect of hip joint muscle strength and size on hip joint angular velocity during 110 m hurdling motion - Okutani, H.; Suga, T.; Wakamiya, M.; Isaka, T.; Nagano, A. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of this study was to investigate the effect of hip joint flexor/extensor strength andsize on hip joint angular velocity during 110 m hurdling motion. To achieve this goal, we determined hip joint angular velocity during hurdling motion with high speed camera. We also measured isokinetic hip joint torque with a dynamometer, and measured the muscle volume of the psoas major muscle and hamstrings of the lead leg side with MRI. There were significant correlations between isokinetic hip joint flexor torque at 0.52 and 1.05 rad/s and hip joint flexion angular velocity (p = 0.04 and p = 0.02, respectively). There were no statistically significant correlations between muscle volume andjoint angular velocity. These results suggested that hip joint flexor strength ispossibly an important factor to swing up the lead leg quickly during hurdling motion.